2022
DOI: 10.1101/2022.04.12.488010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome wide screen of RNAi molecules against SARS-CoV-2 creates a broadly potent prophylaxis

Abstract: Expanding the arsenal of prophylactic approaches against SARS-CoV-2 is of utmost importance, specifically those strategies that are resistant to antigenic drift in Spike. Here, we conducted a screen with over 16,000 RNAi triggers against the SARS-CoV-2 genome using a massively parallel assay to identify hyper-potent siRNAs. We selected 10 candidates for in vitro validation and found five siRNAs that exhibited hyper-potent activity with IC50<20pM and strong neutralisation in live virus experiments. We furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Several studies have already described the design and experimental evaluation of siRNAs against SARS-CoV-2, with some siRNAs being more active than others Khaitov et al, 2021; Idris et al, 2021; Tolksdorf et al, 2021; Niktab et al, 2021; Sohrab et al, 2022b; Yogev et al, 2022; Sohrab et al, 2022a; Friedrich et al, 2022; Chang et al, 2022; Becker et al, 2022; Ambike et al, 2022; Nabiabad et al, 2022. Comparing success rates among diverse studies is not straightforward because of methodological differences between studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have already described the design and experimental evaluation of siRNAs against SARS-CoV-2, with some siRNAs being more active than others Khaitov et al, 2021; Idris et al, 2021; Tolksdorf et al, 2021; Niktab et al, 2021; Sohrab et al, 2022b; Yogev et al, 2022; Sohrab et al, 2022a; Friedrich et al, 2022; Chang et al, 2022; Becker et al, 2022; Ambike et al, 2022; Nabiabad et al, 2022. Comparing success rates among diverse studies is not straightforward because of methodological differences between studies.…”
Section: Resultsmentioning
confidence: 99%
“…To make the comparison as fair and uniform as possible, we compiled the results of ex vivo assessment of siRNAs against SARS-CoV-2 and flagged “high activity” those siRNAs with a significant repressive effect on viral RNA accumulation or viral plaque forming units exceeding 50% in the tested conditions (selecting conditions with siRNA concentrations close to 10 nM and post-transfection incubation close to 48 h whenever possible). The proportion of designed siRNAs with high activity ranges from 0 Sohrab et al, 2022b; Sohrab et al, 2022a to 10/11 Chang et al, 2022 and 1/1 Tolksdorf et al, 2021 (see Figure 4; note that siRNAs designed by Yogev et al, 2022 could not be analyzed because their sequence was not released). Our approach, yielding 6/8 siRNAs with high activity, proved efficient in designing potent siRNAs with a pure bioinformatics approach, without requiring high-throughput experimental screening.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the shRNAs used in this study were designed in May 2020 and the Omicron strain appeared in Nov 2021, the retrospective comparison in Figure 1 showed that the mutation of the SP conserved sequence can also evade shRNA targeting. Therefore, we suggest using the shRNA cocktail to provide better protection or therapeutic effects for COVID-19 [ 31 ]. Four siRNAs have been demonstrated to bind complementary sequences in the SARS-CoV-2 genome and presented in every clinically relevant published SARS-CoV-2 genome, including variants α, β, γ, and Omicron, effectively reducing viral load [ 32 ].…”
Section: Discussionmentioning
confidence: 99%